2017
DOI: 10.1007/s10068-017-0113-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermented red beet extracts on the shelf stability of low-salt frankfurters

Abstract: The effect of fermented red beet (FRB) on shelf-life of low-salt frankfurters stored for 4 weeks was investigated. The pH, volatile basic nitrogen (VBN), lightness, and yellowness of frankfurters decreased with increasing levels of FRB, whereas the redness of frankfurters increased with increasing levels of FRB. The VBN, thiobarbituric acid reactive substance values, total viable count, and redness of all treatments decreased with increasing period of refrigeration storage. The appearance, color, and juiciness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
(47 reference statements)
2
21
0
Order By: Relevance
“…These results are in accordance with a study indicating that the consumer acceptability score of fresh pork sausage with added red beetroot (1 mL/kg) was higher than those of control (no colorant) group sausages [12]. Moreover, some meat products such as low-salt frankfurters with fermented red beet extract (1, 3 and 5%) [37] and emulsified pork sausages with 1% red beet powder [39] exhibited sensory characteristics similar to those of the control.…”
Section: Sensory Evaluation Of Sausagessupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in accordance with a study indicating that the consumer acceptability score of fresh pork sausage with added red beetroot (1 mL/kg) was higher than those of control (no colorant) group sausages [12]. Moreover, some meat products such as low-salt frankfurters with fermented red beet extract (1, 3 and 5%) [37] and emulsified pork sausages with 1% red beet powder [39] exhibited sensory characteristics similar to those of the control.…”
Section: Sensory Evaluation Of Sausagessupporting
confidence: 90%
“…The L* and b* values of the control were the highest, followed by the sausages with beetroot extract, beetroot powder and carmine, respectively. It has been pointed out that fermented red beet added to frankfurters results in lower lightness (L*) and yellowness (b*) values but higher redness (a*) values [37]. Likewise, Sucu and Turp [38] reported that the addition of beetroot powder as a nitrate source into fermented sausages led to a decrease in the L* and b* values of sausages at the beginning of storage (p < 0.05).…”
Section: Physicochemical Properties Of Sausagesmentioning
confidence: 99%
“…Moreover, the inclusion of beetroot powder [8,46,[61][62][63][64][65] and fermented extract [6,15] produces a significant reduction in the residual nitrite. The fermented extracts also lowered microbial contents [6,54] of reformulated products. In contrast, the effect of the use of dehydrated beetroot showed contradictory results for pH values.…”
Section: Application Of Beetroot In Meat Productsmentioning
confidence: 90%
“…These high values confirm that beetroot is a promising source of "naturally occurring" nitrate. In addition, fermenting beetroot juices and extracts would allow us to pre-convert nitrates into nitrites [15,21], which would increase the protective effects, since it would be added to the meat product in the form of nitrite [6,54].…”
Section: Nitrates and Nitritesmentioning
confidence: 99%
See 1 more Smart Citation